OVERVIEW OF AUTOMATION METHODS OF SMALL AND MEDIUM ENGINEERING ENTERPRISES BASED ON CALS-TECHNOLOGIES AND SYSTEMS ENGINEERING APPROACH - Dmitry V. DUDKIN (Advanced Engineering Research, 2010)
The design techniques of integrated information systems development aimed at the life cycle support are reviewed. Cases of the CALS-technologies and systems engineering for building some typical models are considered. These models can be used for typical methods development and creation of the general base for system installation techniques and operating information system intercomparison.